A informática e a educação continuada de professores: analisando aprendizagens e processos - Simião, Lucélio Ferreira (2006)
This research, of a qualitative nature, investigates aspects of the learning process of the teaching staff, in order to contribute to the continued in-service learning for teachers in the use of computers in their teaching practice. The preparation of teachers to work with computers in education has been occurring, usually, by means of courses given outside of the context of their work. However, this study seeks to analyze the possible contribution of a proposal of continuing education in the work place, to make possible new competence and abilities in the use of computers in the classroom. The study was carried out in a private school in the city of São Carlos, SP, and its central focus was the development of activities within the context of the reality of school and teacher, using software applications as teaching tools in the construction of projects. The methodology adopted is associated with a constructive-collaborative model of research and intervention, in which the people involved, teacher and pupil, play roles of a collaborative nature, as partners, in a multi-faceted relationship. The theoretic contribution established a relation among computer science, education and teacher training, emphasizing the advance of technology in education and the roll of the school and the teacher in relation to new and growing educational demands, in a constantly evolving technological scene. The data obtained indicated a concern on the part of the investigated teachers to appropriate for themselves skills that makes it possible for them to use computers in the classroom. They recognize the usefulness of the computer in teaching, however they point out some limitations, such as the lack of ability and the difficulty of developing educational activities using the computer, the lack of time available to learn to use the computer in view of other teaching demands, and the lack of equipment and educational software for use in the class room. It was evident that, in the training environment, the production of innovative educational practices came about through reflection on shared experiences. It was indicated that there is a need for the training programs for teachers to have as their axis the context of their use, and and for the creation of a culture that permits the teacher to become a critical user of technology, using it in her teaching, and becoming her own agent of change.